Varicose vein surgery in elderly patients: What needs to be considered? - Dünnweber, M.; Mumme, A. (Phlebologie, 2017)
The need for invasive therapeutic measures in patients with varicose veins increases in an ageing population. Modern varicose vein surgery is particularly suitable for this age group, precisely because the stage of the disease is often advanced in geriatric patients. Gentle surgical techniques, such as invaginated stripping, cause the least possible operative trauma and are therefore especially suitable for the aged body. Less stressful anaesthetic techniques, such as tumescence, spinal anaesthesia or total intravenous anaesthesia with the use of a laryngeal tube, are likewise particularly well-suited for the treatment of geriatric patients with varicose veins.Special criteria regarding the ASA classification and anticoagulation must be applied when considering the perioperative risk in frequently multimorbid geriatric patients. Very few complications generally occur in patients at ASA stages 1 and 2 and under single anticoagulant therapy, and surgery is feasible even in elderly people. In the case of existing phenprocoumon treatment, bridging should be critically considered on a case-by-case basis. Perioperative prevention and management of hypothermia and special procedures to obtain postoperative convalescence should also be adapted to the particular needs of the elderly patient.
Keywords: Varicose vein surgery, elderly people, indications